Training community engaged climate adaptation leaders using multiple case study analysis: insights from cognitive learning sciences - Abercrombie, Sara; Stuart, Diana Lynne; Aslan, Clare Ellsworth; Souther, Sara; Petersen, Brian Craig (Frontiers in Climate, 2023)
Training community engaged climate adaptation leaders requires developing learners’ thinking skills so they can flexibly approach adaptation planning and problem solving in novel socio-ecological contexts. In this text, we describe how multiple case study analysis helps adult learners in both formal and community education settings develop the thinking skills necessary for adaptation work, including analogical reasoning and knowledge transfer; and we illustrate how to organize multiple case analysis on shared critical competencies aligned to community needs. The article concludes with a discussion of three instructional best practices for employing multiple case analysis in educational settings and a discussion of how this educational approach can guide training programs and funding priorities.